Effects of an antler point restriction on deer hunter perceptions and satisfaction in Missouri. (22nd October 2018) - Hansen, Lonnie P.; Sumners, Jason A.; Reitz, Ron; Bian, Yuanyuan; Gao, Xiaoming; Millspaugh, Joshua J.
ABSTRACT: Antler point restrictions (APR), intended to create an older male age structure of white‐tailed deer ( Odocoileus virginianus ), have been implemented in many states, but effects of APR on hunters' satisfaction and activities often have not been measured. During 2004–2008, we conducted mail surveys of firearms deer hunters in Missouri, USA, to measure effects of an APR on respondents including 1) perceptions of deer population trends and availability of large males; 2) satisfaction with the hunting experience and deer management; and 3) support of the APR. There was no effect of the APR on how respondents perceived deer population trends, but respondents hunting under the APR believed there were more large males in both central and northern Missouri. Respondents were less satisfied with their hunt and deer management in central Missouri areas under the APR during years when hunter success was reduced. There was no effect of the APR on how respondents rated their most recent deer season in the northern areas under the APR, although respondents there were less satisfied with deer management prior to implementation of the APR and for the first 2 years after implementation with no differences after that time. In all areas, generally >70% of respondents supported the APR; presence of the APR where a respondent hunted did not affect support of the APR. Respondents supporting the APR were more likely to have less deer hunting experience, hunt counties where harvest of antlered males was relatively greater, rate Missouri deer management as good or excellent, hunt private land during at least part of the season, and select for antlered males while hunting. An APR may be most appropriate where deer densities are moderate or large and harvest rates of antlered males are excessive. Use of APRs in areas with low‐density deer populations where harvest opportunity is low may not be popular with hunters. © 2018 The Wildlife Society. Abstract : We evaluated deer hunter attitudes toward an antler point restriction intended to reduce excessive harvest rates of male white‐tailed deer and increase harvest of antlerless deer. Hunter support of the antler point restriction was high but hunter satisfaction with hunting seasons and deer management varied annually and geographically and were most closely associated with deer population status and harvest success.